Comparative Kinetic Study of Anaerobic Treatment of Thermally Pretreated Source-Sorted Organic Market Refuse - Aritra Das; Chanchal Mondal (Journal of Engineering)
The present study deals with extensive investigations of the effect of thermal pretreatment on whole-sale market rejects for their biogas production potential. Market reject considered as biomass for this study has been treated at two different temperatures 85°C and 135°C for 8 h each and subjected as feedstock for anaerobic digestion (AD) process. The AD process has been operated in the mesophilic range (35–38°C) of bacterial growth. Various kinetic models have been used to simulate the experimental data. Kinetic modeling revealed that biogas production rate exhibited better coefficient of determination (R2) in the range of 0.973–0.989 with exponential model for the ascending limb whereas the descending limb resulted in good linear correlation with R2 as 0.911–0.976. Logistic growth model and Gompertz relation simulation of cumulative biogas production resulted in better R2 values in the range of 0.994–0.997 and 0.998–0.999, whereas the R2 values for exponential rise to maximum plots ranged from 0.722 to 0.800.